2021
DOI: 10.3847/1538-4357/ac0339
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of a Second Propeller: A High-inclination Twin of AE Aquarii

Abstract: For decades, AE Aquarii (AE Aqr) has been the only cataclysmic variable star known to contain a magnetic propeller: a persistent outflow whose expulsion from the binary is powered by the spin-down of the rapidly rotating, magnetized white dwarf. In 2020, LAMOST J024048.51+195226.9 (J0240) was identified as a candidate eclipsing AE Aqr object, and we present three epochs of time-series spectroscopy that strongly support this hypothesis. We show that, during the photometric flares noted by Thorstensen, the Balme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Two subsequent studies have added additional weight to the connection between J0240+1952 and AE Aqr. Pretorius et al (2021) detected radio emission, with a radio luminosity close to the highest measured of any CV, higher even than AE Aqr, while Garnavich et al (2021) found that the Balmer emission lines broadened up to ±3000 km/s during flares, and showed that a P Cygni-like component in H𝛼, also seen by Thorstensen (2020), was consistent with Wynn et al (1997)'s magnetic propeller model.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Two subsequent studies have added additional weight to the connection between J0240+1952 and AE Aqr. Pretorius et al (2021) detected radio emission, with a radio luminosity close to the highest measured of any CV, higher even than AE Aqr, while Garnavich et al (2021) found that the Balmer emission lines broadened up to ±3000 km/s during flares, and showed that a P Cygni-like component in H𝛼, also seen by Thorstensen (2020), was consistent with Wynn et al (1997)'s magnetic propeller model.…”
Section: Introductionsupporting
confidence: 67%
“…Pretorius et al (2021) searched for optical pulsations down to a period of 10 s, but found no signals above their detection threshold of 1%. Finally, and most stringently of all, Garnavich et al (2021) presented 𝑔 and 𝑖-band photometry taken with the Hale 5 m telescope and Caltech HIghspeed Multi-color camERA (CHIMERA) which had the cadence and the signal-to-noise to detect spin periods with amplitudes as low as 4 mmag (0.43%) in the 𝑔-band over a period range of 6.3 to 85 s, but again found nothing of significance.…”
Section: Introductionmentioning
confidence: 96%
“…This means that J0240+19 is a high inclination system and explains why the He I λ6678 Å emission line briefly disappears at orbital phase 0. Additional photometric observations by Garnavich et al (2021) confirmed the high inclination of J0240+19, but did not detect the WD's spin period. The spin period was finally found by Pelisoli et al (2021) to be 24.9328(38) s with an amplitude of 0.2% in the g-band, which is below the detection limits of the previous searches.…”
Section: Introductionmentioning
confidence: 88%
“…The spectrum of J0240+19 obtained during the first observation is shown in Figure 1. This observation occured between orbital phases 0.70-0.78 using the ephemeris of Garnavich et al (2021). The average flux density and standard deviations for each frequency band are shown in black.…”
Section: Spectroscopymentioning
confidence: 96%
See 1 more Smart Citation